2023
DOI: 10.31661/jbpe.v0i0.2011-1234
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Low Frequency-Electromagnetic Fields (ELF-EMF) Can Decrease Spermatocyte Count and Motility and Change Testicular Tissue

Abstract: Background: Substantial evidence indicates that exposure to extremely low frequency-electromagnetic fields (ELF-EMFs) affects male reproductive system. Objective:The goal of this study was to evaluate the effects of long-term irradiation with ELF-EMF on sperm quality and quantity and testicular structure. Material and Methods:In this case-control study, sixty male Sprague-Dawley rats were randomly divided into six groups. Experimental groups were exposed to ELF-EMF (50 Hz EMF, 100 µT) for either 1 h/day for 52… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…A trend toward a dose-response relationship was found in leukemia with SIRs of 1.8 (95% CI, 1.1-2.8), 1.4 (95% CI, 0.81-2.2), 1.1 (95% CI, 0.81-2.2) and 1.1 (95% CI, 0.70-1.6) for the exposure categories of high magnetic, electrical, medium magnetic and low magnetic, respectively [33]. It was revealed that ELF-EMFs may reduce the number and motility of spermatocytes, as well as cause structural changes in testicular tissue [34]. It was found that radiologists who used intrauterine contraceptives while they were occupationally exposed to CMF from MRI scanners reported about abnormal uterine bleeding more often than not exposed to CMF radiologists [35].…”
Section: Discussionmentioning
confidence: 97%
“…A trend toward a dose-response relationship was found in leukemia with SIRs of 1.8 (95% CI, 1.1-2.8), 1.4 (95% CI, 0.81-2.2), 1.1 (95% CI, 0.81-2.2) and 1.1 (95% CI, 0.70-1.6) for the exposure categories of high magnetic, electrical, medium magnetic and low magnetic, respectively [33]. It was revealed that ELF-EMFs may reduce the number and motility of spermatocytes, as well as cause structural changes in testicular tissue [34]. It was found that radiologists who used intrauterine contraceptives while they were occupationally exposed to CMF from MRI scanners reported about abnormal uterine bleeding more often than not exposed to CMF radiologists [35].…”
Section: Discussionmentioning
confidence: 97%